Dominant effect of particle size on the CeO2 preferential evaporation during plasma spraying of La2Ce2O7. Issue 4 (April 2017) - Wang, Li-Shuang; Zhang, Shan-Lin; Liu, Tao; Li, Chang-Jiu; Li, Cheng-Xin; Yang, Guan-Jun
Abstract: The inhomogeneous composition distribution of atmospheric plasma sprayed La2 Ce2 O7 limits its operation in thermal barrier coatings. Two types of La2 Ce2 O7 powders were used to investigate the effect of the powder size and structure on the preferential evaporation of Ce during plasma spraying. The results indicate that powder particle size is dominant for the Ce evaporation loss. Such effect is significantly intensified with the decrease of particle size. When the particle size is larger than 30 μm, the Ce loss is less or can be neglected. Two mechanisms including the element diffusion mechanism and convection mass transfer mechanism are proposed to well explain the evaporation rule. Moreover, the loss of Ce is higher using the agglomerate-sintered powder due to its higher thermal conductivity than the as-agglomerated powder. Correspondingly, the CeO2 loss can be neglected in the coatings as the agglomerated powders with a size <30 μm were used.